Flash 5 for Windows and Macintosh - Ulrich, Katherine (Peachpit Press, 2001)
This book introduce the Flash editor, creating simple graphics. Modifying simple graphics. Animation with motion tweening. Animation with shape tweening, more-complex animation tasks...